Two new cytochalasan derivatives from Chaetomium globosum SNSHI-5, a fungus derived from extreme environment. Issue 14 (18th July 2017) - Wang, Xiao-Yan; Yan, Xia; Fang, Mei-Juan; Wu, Zhen; Wang, Dong; Qiu, Ying-Kun
Abstract: Two new cytochalasan derivatives, isochaetoglobosin Db (1 ) and cytoglobosin Ab (2 ), were isolated from an ethyl acetate extract of Chaetomium globosum SNSHI-5, a fungus derived from extreme environment. The structures of the new compounds were comprehensively characterized by HR-ESI-MS, 1 H NMR, 13 C NMR and 2D-NMR. Cytotoxic activity against H292 human lung cancer cell of the new compounds was tested. Isochaetoglobosin Db (1 ) showed potent cytotoxicity with IC50 of 3.5 μM, while cytoglobosin Ab was inactive (IC50  > 10 μM). Graphical Abstract: